A Passage to Infinity: Medieval Indian mathematics from kerala and its impact - Joseph, George Ghevershese
This book traces the first faltering steps taken in the mathematical theorization of infinity which marks the emergence of modern mathematics. It analyzes the part played by Indian mathematics through the Kerala conduit, which is an important but neglected part of the history of mathematics.
Keywords: Mathematics-India-Kerala--History. Mathematics, Medieval. Astronomy, Medieval-India-Kerala.